The Identity of Thalictrum confine (Ranunculaceae) - R. S. Mitchell (Brittonia, 1988)
A history of the collecting and naming ofThalictrum confine Fern, is detailed in an attempt to clear up long-standing nomenclatural and taxonomic confusions.Thalictrum confine has traditionally been distinguished fromT. venulosum Trel. on the basis of its larger, falcate fruits; however the lectotype ofT. confine consists only of a packet of terete, subcylindric fruits, even smaller than those of the type specimen ofT. venulosum. Fernald's original description ofT. confine also does not match large-fruited plants which he later referred to that species. Those plants first cited by him asT. occidentale A. Gray, and later distributed as Gray Herbarium exisccatae under the nameT. confine, match specimens, presently found at the type location ofT. confine. Although fruit-growth was apparently arrested by forst-damage in the lectotype, it is perceived to represent the larger-fruited plants as well.Thalictrum confine is placed in synonymy under polymorphicT. venulosum. Acceptance of infraspecific taxa in the group is discouraged, but, for those who wish to segregate larger-fruited trans-Canadian plants, the correct varietal name isT. venulosum var.confine (Fern) B. Boivin, withT. turneri B. Boivin in synonymy.
Keywords: biology